Exercise and adiposity in overweight and obese children and adolescents: a systematic review with network meta-analysis of randomised trials - Russell R Pate; George A Kelley; Kristi S Kelley (BMJ Open)
Objectives Determine both the effects and hierarchy of effectiveness for exercise interventions (aerobic, strength training or both) on selected measures of adiposity (body mass index (BMI) in kg/m2, fat mass and per cent body fat) in overweight and obese children and adolescents.Design Network meta-analysis of randomised exercise intervention trials.Setting Any setting where a randomised trial could be conducted.Participants Overweight and obese male and/or female children and adolescents 2–18 years of age.Interventions Randomised exercise intervention trials>4 weeks, published between 1 January 1973 and 22 August 2018, and which included direct and/or indirect evidence for aerobic, strength training or combined aerobic and strength training.Primary outcomes Changes in BMI in kg/m2, fat mass and per cent body fat.Results Fifty-seven studies representing 127 groups (73 exercise, 54 control) and 2792 participants (1667 exercise, 1125 control) met the criteria for inclusion. Length of training (X- ± SD) averaged 14.1±6.2 weeks, frequency, 3.3±1.1 days per week and duration 42.0±21.0 min per session. Significant and clinically important reductions in BMI, fat mass and per cent body fat were observed in aerobic versus control comparisons (BMI, mean, 95% CI -1.0, 1.4 to −0.6; fat mass -2.1, –3.3 to −1.0 kg; per cent fat -1.5, –2.2 to −0.9%) and combined aerobic and strength versus control comparisons (BMI -0.7, –1.4 to −0.1; fat mass -2.5, –4.1 to −1.0 kg; per cent fat, -2.2, –3.2 to −1.2%). A significant reduction in per cent fat was also found for strength vs control comparisons (-1.3,–2.5 to −0.1%). Combined aerobic and strength training was ranked first for improving both fat mass (kg) and per cent body fat while aerobic exercise was ranked first for improving BMI.Conclusions Aerobic and combined aerobic and strength training are associated with improvements in adiposity outcomes in overweight and obese children and adolescents.PROSPERO registration number CRD42017073103.